A kind of symbiotic bismuth-based layered ferroelectric Bi 7 Ti 4 NbO 21 Semiconductor material preparation method and application thereof

Synthesis of symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO21 semiconductor material by solvent thermal method solves the problem of high energy consumption and difficulty in regulating the morphology of the high-temperature solid phase method in the prior art, and achieves efficient synthesis of the material and excellent photocatalytic properties.

CN116639729BActive Publication Date: 2025-03-21YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310609389.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-29
Publication Date
2025-03-21
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

The synthesis of existing bismuth-based layered ferroelectric semiconductor materials mostly uses high-temperature solid phase methods, which consumes high energy and is difficult to regulate morphology and microstructure, resulting in insufficient specific surface area and active sites of the material, and poor ferroelectric and photocatalytic properties.

Method used

Solvent Thermal method was used to synthesize symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO21 semiconductor material. By heating reaction in a hydrothermal kettle, the reaction temperature and time were controlled, and combined with the use of alkali solution, materials with large specific surface area and rich active sites were prepared.

Benefits of technology

It realizes efficient synthesis of materials, has high stability and excellent photocatalytic properties, and especially shows high photocatalytic activity during CO2 photoreduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116639729B_ABST
    Figure CN116639729B_ABST
Patent Text Reader

Abstract

The invention discloses a symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 The preparation method and application of semiconductor materials include the following steps: step 1: adding bismuth source, Nb2O5 and titanium source into water according to stoichiometric ratio and stirring evenly; step 2: then pouring alkaline solution into the mixed solution obtained in step 1 and continuing to stir evenly; step 3: then transferring the mixed solution obtained in step 2 into a hydrothermal kettle for heating reaction; step 4: washing and drying the product obtained in step 3, namely, the symbiotic ferroelectric Bi7Ti4NbO 21 Semiconductor material. The present invention uses a solvent thermal method to synthesize a bismuth-based layered symbiotic ferroelectric Bi7Ti4NbO with a large specific surface area, rich active sites, complete crystal form, uniform particle size dispersion, strong ferroelectric properties and excellent photocatalytic properties. 21 Semiconductor materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a symbiotic bismuth-based layered ferroelectric material, in particular to a symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 Preparation methods and applications of semiconductor materials. Background Art

[0002] With the rapid development of global industrialization and modernization, excessive carbon dioxide emissions have broken the balance of the natural carbon cycle, causing serious environmental problems, especially global warming. The conversion of carbon dioxide into high-value-added carbon-containing fuels driven by solar energy has become one of the hot topics of scientific research because of its advantages in solving both carbon emissions and energy crises. So far, although great progress has been made in carbon dioxide reduction, the practical application of carbon dioxide photoreduction in solar fuels is far from satisfactory. Therefore, it is of great significance to explore the synthesis of new photocatalysts with efficient photocatalytic performance.

[0003] In recent years, bismuth-based layered perovskite ferroelectric materials (BLSFs) have been widely studied and reported for their excellent fatigue performance and ferroelectric properties. 12 and Bi3TiNbO9 have been reported to exhibit excellent photocatalytic activity. In order to further improve the photocatalytic performance of the material, researchers have also proposed many modification methods, such as the regulation of morphology and crystal plane, the construction of defect engineering, the doping / substitution of A and B sites, the formation of a multi-component mixed system solid solution, etc. It is well known that the spontaneous polarization electric field of ferroelectric semiconductor materials can effectively reduce the recombination of electrons and holes, thereby improving the photocatalytic performance. Therefore, the ferroelectric properties of the material can be improved by effective means to improve the photocatalytic performance. It is reported that the use of two different bismuth-based layered structural units to form a new material-symbiotic bismuth-based layered ferroelectric semiconductor can significantly improve the ferroelectric properties of the material. However, the synthesis of bismuth-based layered ferroelectric semiconductors currently mostly uses high-temperature solid-phase methods. The synthesis process is not only energy-intensive, but also often difficult to achieve morphology and microstructure regulation. Therefore, how to use the solvothermal method to synthesize a bismuth-based layered ferroelectric Bi7Ti4NbO with a large specific surface area, rich active sites, strong ferroelectric properties and photocatalytic properties? 21 Semiconductor materials and their application in the field of photocatalysis have important research value. Summary of the invention

[0004] Purpose of the invention: In view of the above-mentioned prior art, a symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO is proposed. 21The preparation method of semiconductor materials uses a solvent thermal method to synthesize bismuth-based layered ferroelectric Bi7Ti4NbO with large specific surface area, rich active sites, strong ferroelectric properties and photocatalytic properties. 21 Semiconductor materials.

[0005] Technical solution: A symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 A method for preparing a semiconductor material comprises the following steps:

[0006] Step 1: Add bismuth source, Nb2O5 and titanium source into water according to the stoichiometric ratio and stir evenly;

[0007] Step 2: Then pour the alkaline solution into the mixed solution obtained in step 1 and continue to stir evenly;

[0008] Step 3: Then, the mixed solution obtained in step 2 is transferred to a hydrothermal kettle for heating reaction;

[0009] Step 4: Wash and dry the product obtained from the reaction in step 3 to obtain the symbiotic ferroelectric Bi7Ti4NbO 21 Semiconductor materials.

[0010] Furthermore, in step 1, the bismuth source is a bismuth salt selected from at least one of bismuth nitrate pentahydrate, bismuth sulfate, bismuth chloride, and bismuth citrate.

[0011] Furthermore, in step 1, the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, and titanium tetrachloride.

[0012] Furthermore, in step 2, the alkaline solution is selected from at least one of sodium hydroxide and potassium hydroxide, and the alkaline concentration of the alkaline solution in the entire reaction solution is 3-6 mol / L.

[0013] Furthermore, in step 3, the reaction temperature is 200-240° C. and the reaction time is 20-30 h.

[0014] Furthermore, in step 4, the product is washed three times with anhydrous ethanol and three times with deionized water respectively and centrifuged several times.

[0015] Furthermore, in step 4, drying is performed at 50-70° C. for 12-24 h.

[0016] The symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO prepared by the method 21 Semiconductor materials.

[0017] The symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 Application of semiconductor materials as ferroelectric materials in photocatalysis.

[0018] Furthermore, the photocatalysis includes photocatalytically reducing CO2 to carbon-containing fuels, cracking water to obtain hydrogen and oxygen, and degrading pollutants in water. Beneficial Effects

[0019] 1. The present invention synthesizes the intergrowth bismuth-based layered ferroelectric Bi7Ti4NbO by a solvothermal method 21 Semiconductor material, the preparation method is simple to operate, low cost, does not require high temperature reaction process and complex reagents, the reactants have a large specific surface area, rich active sites, complete crystal form, uniform particle size dispersion, and high stability.

[0020] 2. Symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO prepared by the present invention 21 Semiconductor materials have excellent photocatalytic properties, especially in the process of photocatalytic reduction of CO2 to CO, they have high photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns of photocatalytic materials prepared in Examples and Comparative Examples;

[0022] Figure 2 SEM images of photocatalytic materials prepared in Examples and Comparative Examples;

[0023] Figure 3 The CO yield bar graph of the photocatalytic materials prepared in the examples and comparative examples;

[0024] Figure 4 Flow chart of the preparation method of the embodiment. DETAILED DESCRIPTION

[0025] The present invention is further explained below in conjunction with the accompanying drawings. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The methods described are conventional methods unless otherwise specified. The materials described can be obtained from public commercial channels unless otherwise specified.

[0026] The following example Bi7Ti4NbO 21 And the comparative example Bi4Ti3O 12 , the performance evaluation method of Bi3TiNbO9 is as follows:

[0027] Bi4Ti3O 12 、Bi3TiNbO9、Bi7Ti4NbO 21 Phase evaluation method:

[0028] X-ray diffraction (XRD): The prepared Bi4Ti3O 12 、Bi3TiNbO9、Bi7Ti4NbO 21The crystal structure of the samples was analyzed using a D8 Advance series wide-angle X-ray diffractometer from Bruker, Germany, with a scanning speed of 5° / min and a scanning range of 20° to 70°.

[0029] Bi4Ti3O 12 、Bi3TiNbO9、Bi7Ti4NbO 21 Microscopic morphology evaluation method:

[0030] Scanning electron microscopy (SEM): The prepared Bi4Ti3O 12 、Bi3TiNbO9、Bi7Ti4NbO 21 The materials were tested on a JSM-IT300 series scanning electron microscope of JEOL, Japan, with an accelerating voltage of 5-20 kV.

[0031] Bi4Ti3O 12 、Bi3TiNbO9、Bi7Ti4NbO 21 CO2 reduction performance evaluation method:

[0032] The photocatalytic CO2 reduction experiments were carried out in a custom-made quartz glass reactor (300 mL). 50 mg of Bi7Ti4NbO 21 Evenly dispersed on a customized quartz glass reactor, and a triangular glass support was placed at the bottom of the reactor. Then 1.0900 g NaHCO3 was placed at the bottom of the reactor and evacuated. Subsequently, 10 mL H2SO4 (0.65 mol / L) was injected into the bottom of the reactor to react with NaHCO3 powder to generate CO2 (1 atm). A xenon lamp (300 W) was used as the light source (Beijing Bofeilai Technology Co., Ltd.), and the reactor temperature was maintained at 20 °C through a condensation cycle. Finally, a GC7920 gas chromatograph (Beijing Huaguang Education Technology Co., Ltd.) was used to qualitatively and quantitatively analyze 1 mL of the reaction gas extracted every hour, and the reaction lasted for 4 hours.

[0033] Bi4Ti3O 12 The evaluation method of CO2 reduction performance of Bi3TiNbO9 is consistent with the above.

[0034] Example 1 Preparation of symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 Semiconductor materials and their performance testing

[0035] like Figure 4As shown, at room temperature, 3.3955 g Bi(NO3)3·5H2O, 1.3700 ml tetrabutyl titanate, and 0.1329 g Nb2O5 were first dispersed in a beaker containing 30 mL of deionized water and stirred, then 9.600 g NaOH was dissolved in 30 mL of deionized water and poured into the above reaction solution to continue magnetic stirring, and finally the resulting mixture was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and heated for reaction at a temperature of 220 °C for 24 h. After the reaction, it was washed and centrifuged three times with anhydrous ethanol and deionized water, and dried at 60 °C for 12 h to obtain the intergrown layered bismuth ferroelectric Bi7Ti4NbO 21 Semiconductor materials.

[0036] Take the prepared symbiotic Bi7Ti4NbO 21 The gas-solid phase photocatalytic CO2 reduction experiment was carried out with 50 mg of photocatalytic material. The CO yield was 11.92 μmol g under full light irradiation for 4 h. -1 .

[0037] XRD spectrum Figure 1 As shown; SEM images are shown Figure 2 As shown; CO production rate is Figure 3 shown.

[0038] Comparative Example 1 Preparation of Bismuth-based layered ferroelectric Bi4Ti3O 12 Semiconductor materials and their performance testing

[0039] At room temperature, 1.9400 g Bi(NO3)3·5H2O and 1.02 ml tetrabutyl titanate were first dispersed in a beaker containing 30 mL of deionized water and stirred. Then 9.600 g NaOH was dissolved in 30 mL of deionized water and poured into the above reaction solution and continued to be magnetically stirred. Finally, the resulting mixture was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and heated for reaction at 180 °C for 24 h. After the reaction, it was washed and centrifuged three times with anhydrous ethanol and deionized water, and dried at 60 °C for 18 h to obtain the intergrown layered bismuth ferroelectric Bi4Ti3O 12 Semiconductor materials.

[0040] Take the prepared Bi4Ti3O 12 50 mg of photocatalytic material was used for gas-solid phase photocatalytic CO2 reduction experiment. Under full light irradiation for 4 h, the CO yield was 6.48 μmol g -1 .

[0041] XRD spectrum Figure 1 As shown; SEM images are shown Figure 2 As shown; CO production rate is Figure 3 shown.

[0042] Comparative Example 2 Preparation of Bismuth-based layered ferroelectric Bi3TiNbO9 material and its performance test

[0043] At room temperature, 1.4550 g Bi(NO3)3·5H2O, 0.3500 ml tetrabutyl titanate, and 0.1329 g Nb2O5 were first dispersed in a beaker containing 30 mL of deionized water and stirred, then 4.8000 g NaOH was added and magnetic stirring was continued, and finally the resulting mixture was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and heated for reaction at 220 °C for 24 h. After the reaction, the mixture was washed and centrifuged three times with anhydrous ethanol and deionized water, and dried at 60 °C for 12 h to obtain the symbiotic layered bismuth-based ferroelectric Bi3TiNbO9 semiconductor material.

[0044] 50 mg of the prepared Bi3TiNbO9 photocatalytic material was used for gas-solid phase photocatalytic CO2 reduction experiment. Under full light irradiation for 4 h, the CO yield was 8.59 μmol g -1 .

[0045] XRD spectrum Figure 1 As shown; SEM images are shown Figure 2 The CO production rate is shown as Figure 3 shown.

[0046] for Figure 1 By XRD test of the samples, Example 1, Comparative Example 1 and Comparative Example 2 were respectively 21 、Bi4Ti3O 12 Corresponding to the standard cards PDF﹟(31-0202), PDF﹟(43-0973), and PDF﹟(39-0233) of Bi3TiNbO9, it shows that the synthesized catalyst is pure phase without other impurities.

[0047] for Figure 2 Through SEM testing of the samples, it can be found that the three catalysts synthesized by the solvothermal method are all nanoflower balls formed by stacking of sheet-like nanosheets. The thickness of the samples ranges from about 15 to 50 nm. In addition, it can be clearly seen that the co-growth Bi7Ti4NbO 21 The sheets are larger and thinner. Under the irradiation of the same light source of equal mass, the symbiotic material exposes more active sites, increasing the contact probability between the substrate and CO2, thereby realizing photocatalytic CO2 reduction.

[0048] The present invention discloses a symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 Photocatalytic principle of conductor materials: Symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21The photocatalytic CO2 reduction reaction of semiconductor materials can be divided into the following three main processes. The first is the light absorption process. When the symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 When the semiconductor material is exposed to light, the electrons in the valence band jump to the conduction band, and holes are generated in the valence band; then the photogenerated electron-hole pairs migrate to the surface of the material and undergo redox reactions with CO2 and H2O, resulting in the symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 Due to the large spontaneous polarization electric field inside semiconductor materials, they can serve as a powerful driving force to promote the effective separation of electrons and holes, thereby improving the activity of photocatalytic reactions; finally, the CO2 adsorbed on the surface of the material is directly reduced to CO through the electron / proton transfer process and the conversion process of intermediate products.

[0049] for Figure 3 By testing the photocatalytic CO2 reduction performance of the samples, it can be seen that after 4 h of illumination, the Bi7Ti4NbO 21 And the comparative example Bi4Ti3O 12 The CO yields of Bi3TiNbO9 were 11.92 μmol g -1 , 6.48 μmol g -1 , 8.59 μmol g -1 .

[0050] It can be seen that the present invention proposes a solvothermal method to synthesize the intergrowth bismuth-based layered ferroelectric Bi7Ti4NbO 21 Semiconductor materials have excellent photocatalytic CO2 reduction performance. Example 2

[0051] At room temperature, 2.4715 g Bi2(SO4)3, 0.3195 g TiO2, and 0.1329 g Nb2O5 were first dispersed in a beaker containing 30 mL of deionized water and stirred, then 10.0998 g KOH was dissolved in 30 mL of deionized water and poured into the above reaction solution and continued to be magnetically stirred. Finally, the resulting mixture was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for heating reaction at a temperature of 200 °C for 30 h. After the reaction, it was washed and centrifuged three times with anhydrous ethanol and deionized water, and dried at 50 °C for 24 h to obtain the intergrown layered bismuth ferroelectric Bi7Ti4NbO 21 Semiconductor materials.

[0052] Take the prepared symbiotic Bi7Ti4NbO 21 50 mg of the photocatalytic material was used for gas-solid phase photocatalytic CO2 reduction experiment. Under full light irradiation for 4 h, the CO yield was 12.56 μmol g -1 . Example 3

[0053] At room temperature, 2.2073 g BiCl3, 0.7587 g TiCl4, and 0.1329 g Nb2O5 were first dispersed in a beaker containing 30 mL of deionized water and stirred, then 20.1996 g KOH was dissolved in 30 mL of deionized water and poured into the above reaction solution for continued magnetic stirring, and finally the resulting mixture was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for heating reaction at a temperature of 240 °C for 20 h. After the reaction, it was washed and centrifuged three times with anhydrous ethanol and deionized water, and dried at 70 °C for 12 h to obtain the symbiotic layered bismuth-based ferroelectric Bi7Ti4NbO 21 Semiconductor materials.

[0054] Take the prepared symbiotic Bi7Ti4NbO 21 The gas-solid phase photocatalytic CO2 reduction experiment was carried out with 50 mg of photocatalytic material. The CO yield was 10.38 μmol g under full light irradiation for 4 h. -1 . Example 4

[0055] At room temperature, 2.7866 g C6H5BiO7, 1.3700 ml tetrabutyl titanate, and 0.1329 g Nb2O5 were first dispersed in a beaker containing 30 mL of deionized water and stirred, then 9.600 g NaOH was dissolved in 30 mL of deionized water and poured into the above reaction solution to continue magnetic stirring, and finally the resulting mixture was transferred to a stainless steel hydrothermal autoclave lined with polytetrafluoroethylene for heating reaction at a temperature of 220 °C for 24 h. After the reaction, it was washed and centrifuged three times with anhydrous ethanol and deionized water, and dried at 60 °C for 18 h to obtain the symbiotic layered bismuth-based ferroelectric Bi7Ti4NbO 21 Semiconductor materials.

[0056] Take the prepared symbiotic Bi7Ti4NbO 21 The gas-solid phase photocatalytic CO2 reduction experiment was carried out with 50 mg of photocatalytic material. The CO yield was 12.03 μmol g under full light irradiation for 4 h. -1 .

[0057] The Bi7Ti4NbO prepared above 21 Photocatalytic materials are also used to photocatalytically split water to obtain hydrogen and oxygen and degrade various pollutants in water.

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO 21 A method for preparing a semiconductor material, characterized in that: The following steps are involved: Step 1: Add bismuth source, Nb2O5 and titanium source into water according to the stoichiometric ratio and stir evenly; Step 2: Then pour the alkaline solution into the mixed solution obtained in step 1 and continue to stir evenly; Step 3: Then, the mixed solution obtained in step 2 is transferred to a hydrothermal kettle for heating reaction; Step 4: Wash and dry the product obtained from the reaction in step 3 to obtain the symbiotic ferroelectric Bi7Ti4NbO 21 Semiconductor materials; In step 1, the bismuth source is a bismuth salt selected from at least one of bismuth nitrate pentahydrate, bismuth sulfate, bismuth chloride, and bismuth citrate; In step 1, the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, and titanium tetrachloride; In step 2, the alkaline solution is selected from at least one of sodium hydroxide and potassium hydroxide, and the alkaline concentration of the alkaline solution in the entire reaction solution is 3-6 mol / L; In step 3, the reaction temperature is 200-240°C and the reaction time is 20-30 h; In step 4, the product was washed with anhydrous ethanol and deionized water for 3 times each and centrifuged several times; In the step 4, drying is performed at 50 to 70° C. for 12 to 24 hours.

2. The symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO prepared by the method according to claim 1 21 Semiconductor materials.

3. The symbiotic bismuth-based layered ferroelectric Bi7Ti4NbO according to claim 2 21 The invention relates to the application of semiconductor materials as ferroelectric materials in photocatalysis; the photocatalysis comprises photocatalytic reduction of CO2 to CO.